Antecedents and Consequences of Employee Engagement in the Digital Era - Akimas , Hari Nugroho; Claudia, Meiske (East Asian Journal of Multidisciplinary Research, 2024)
The study intends to be a model of employee engagement in the digital era. The term "digital" is related with its evolution. Aspects of the study included the pattern of the grand theory employed, the pattern of the unit of analysis, the pattern of the antecedents and effects of employee engagement, the pattern of methodologies and techniques employed, and research gaps that must be addressed in the future. ScienceDirect and Sage Open Journal data were used. The filtering used rayyan.ai and thematic reading with Nvivo 12 plus, resulted in the discovery of 22 relevant publications. As a result, there is a need to investigate cross-management impacts, larger environmental influences, and gender issues. Search engine constraints, a lack of detail in describing gaps, and the degree of effect are all mentioned. Future research areas were also indicated, including the need for meta-analysis and more detailed study on the given gap patterns